The impact of dysmenorrhea on the learning process of adolescent girls - Siahaan, Fridani Krisda; Sari, Utin Siti Candra; Damayanti, Dini Fitri (ELECTRON (Journal of Science and Technology), 2024)
Dysmenorrhea is a menstrual pain condition that can interfere with women's daily activities and overall quality of life. Women of reproductive age frequently experience dysmenorrhea, which may cause them to take breaks from work, school, or routine tasks for several hours or even several days. According to the World Health Organization (WHO), approximately 1,769,425 women (90%) experience dysmenorrhea, and 10%–15% of them report severe symptoms. These severe cases lead to functional limitations, with around 15% of adolescent girls reporting restricted activities due to dysmenorrhea. This study aimed to determine the effect of dysmenorrhea on the learning process of adolescent girls. The research employed an analytic observational design with a cross-sectional approach. Primary data were collected through direct observation using standardized observation sheets. Data analysis included univariate and bivariate procedures, and the Chi-Square test was used to assess the relationship between dysmenorrhea and learning-related outcomes. The results showed a significant association between dysmenorrhea and the learning process of adolescent girls (p = 0.001), indicating that dysmenorrhea adversely affects students’ ability to focus, participate, and perform optimally in the classroom at SMP Negeri 21 Pontianak.